Brazilian congress and foreign affairs: Abdication or delegation? - Leany Barreiro Lemos (University of Oxford, Global Economic Governance Programme (GEG), 2010)
Brazil is playing an increasingly important role globally and thus getting attention from a wide set of observers and practitioners - from academics and policy makers to businesses. Nevertheless, its foreign policy continues to be pursued and implemented in a much insulated fashion, almost entirely through the hands of the executive branch - the president and a set of ministries and agencies, where interests make themselves apparent -, without much participation of the Brazilian Congress. It is considered to be a remarkable case of abdication of power (Lima and Santos, 1998). But is it real abdication, or a case of delegation of powers? Here, I argue in favour of the latter case, siding with those that see Congress as more than pure spectator (Maia and Cesar, 2004; Neves, 2003; Diniz and Ribeiro, 2008; Diniz, 2009).
Keywords: 330; Gesellschaftsordnung; Wirtschaftsordnung; Demokratie; Außenpolitik; Brasilien